Earnings polarization, ethnicity, and regional perspective in Indonesia - Arip Muttaqien; Denisa Sologon; Cathal O'Donoghue (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Recently, quantitative methods have been increasingly used in ethnicity research, which traditionally has relied mainly on qualitative methods. However, quantitative studies on ethnicity in Indonesia are scarce, even though the country has more than 600 ethnic groups living across some 17 thousand islands and a history of ethnic conflicts in several regions. This study aims to address the earnings polarization in Indonesia, which is interwoven with social problems, ethnic conflicts, and social tensions. In particular, we examine the impact of ethnic diversity on earnings polarization in the Indonesian labour market using Re-centered Influence Function regression approach. With considering additional covariates, the results show that regional characteristics are more important than ethnicity. Finally, ethnicity becomes not significant anymore by including the interaction effect between ethnicity and regional characteristics.
Keywords: J08; O53; 330; ethnicity; earnings polarization; regional characteristics; Indonesia